Effect of hydatid cyst antigens on inhibition of melanoma cancer growth in mouse model - Rostami rad, Shahla; Daneshpour, Shima; Mofid, Mohammad reza; Andalib, Alireza; Eskandariyan, Abbasali; Yousofi Darani, Hossein (Cellular and Molecular Biology, 2018)
Cancer is the main cause of death in the developed countries. There are some scientific evidences indicating that parasitic infections induce antitumor activity against certain types of cancers. Hydatid cyst is the larval stage of Echinococcus granulosus, which causes hydatidosis in human and livestock. We have already shown that vaccination of mice with hydatid cyst crude antigens and subsequently challenge them with cancer cells, causes inhibition of melanoma cancer growth. In this study, therapeutic effects of hydatid cyst antigens on C57/black mice that had already been challenged with melanoma tumor were investigated. In this experimental study, 6 groups of C57 black mice were subcutaneously inoculated with melanoma cancer cells (line B16F10) in PBS inside their chest site. After 2 weeks case groups were injected with hydatid cyst fluid, a fraction of cyst fluid, live protoscolices or BCG. control groups were injected with alum alone and other control group was left intact without any intervention. The size of each tumor was measured in all mice. Blood samples were also taken to estimate Interleukin-2 (IL-2), Tumor necrosis factor alpha (TNF-Î±), Interferon gamma (IFN-Î³) and Interleukin-4 (IL-4) levels. Treatment of mice bearing melanoma cancer with hydatid cyst antigens resulted in inhibition of tumor growth and the difference between mean size of tumor in case and control groups was statistically significant. Also, according to our results mean level of measured cytokines between case and control groups was statistically different. Hydatid cyst antigens have anti-melanoma activities and this effect may be related to immune response to parasite antigens.